Marriage as a Mechanism of Power in Regency Era in Quinn’s Bridgerton the Duke and I - Putri Ayresti Sukmaningsih; Rahayu Puji Haryanti (Universitas Islam Negeri Palopo, 2026)
This study examines marriage as a mechanism of power in the Regency Era in Julia Quinn’s novel Bridgerton: The Duke and I (2000). It explores the representation of marriage in the novel, the construction of power through marriage, and the implications of this construction for women’s positions. This study employs a qualitative approach through close textual analysis using John Stuart Mill’s liberal feminist theory. The primary data are obtained from the novel, and the secondary data are taken from journal articles, books, and other sources related to the topic. The findings show that marriage is not just an individual’s relationship, but it is also portrayed as a social tradition, a life purpose, a continuation of lineage, and an economic status. Through its romantic narrative, marriage eventually operates as a form of power in Regency society through social pressure, reproductive obligations, legal and economic authority, and limitations on women’s life choices. This power construction shapes women’s positions, thus leading some female characters to resist rather than passively accept this marriage power. This study suggests that marriage in the novel is not only depicted as a romantic relationship but also as a mechanism of power that shapes women’s lives.